Peran Metode Pembelajaran Diskusi dalam Menciptakan Keaktifan Belajar Siswa di MAS Tarbiyatul Islamiyah - Ujang Ruslandi; Siti Qomariyah; Mimit Sumitra (Katalis Pendidikan : Jurnal Ilmu Pendidikan dan Matematika, 2025)
The discussion method is an effective learning strategy for enhancing student engagement in the learning process. In this process, the teacher's role is crucial in creating an environment that supports active interaction and collaboration among students. This study identifies several key roles of the teacher in the discussion method, including being a facilitator, topic organizer, process guide, and feedback provider. The research findings indicate that teachers who actively facilitate discussions can increase student participation, develop critical thinking skills, and create a positive learning atmosphere. By effectively applying the discussion method, teachers can maximize students' potential in achieving the desired learning objectives.